2014
DOI: 10.33182/ml.v11i3.222
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Turkish migrants and their descendants in Austria Patterns of exclusion and individual and political responses

Abstract: Turkish immigrants and their descendants have become the main target of anti-immigrant political mobilization in Austria since the 1990s. They have come to epitomize the image of the Oriental enemy and the Muslim other. Based on these discursive constructions, Muslims in general, and Turks in particular, have often been described as unwilling to integrate into Austrian society. The articles in this special issue show not only that these discourses and exclusionary attitudes may result in discriminatory practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Furthermore, we showed factors such as education, occupation, gender, age, language skills, and industry affiliation to merely explain a part of the differences between Austrian natives and migrants' class affiliations. This is an important finding and gives rise to the issue of discrimination in Vienna (Sievers et al, ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, we showed factors such as education, occupation, gender, age, language skills, and industry affiliation to merely explain a part of the differences between Austrian natives and migrants' class affiliations. This is an important finding and gives rise to the issue of discrimination in Vienna (Sievers et al, ).…”
Section: Resultsmentioning
confidence: 87%
“…These migrants are better educated than both the “classic” labour migrants of the 1960s and 1970s and the average native Viennese population. The “classic” labour migrants, for example, Turkish and ex‐Yugoslav groups, face risks of downward mobility in Vienna: their incomes are approximately one third lower than the average as they experience educational disadvantage and severe discrimination (Sievers, Atac, & Schnell, ; Verwiebe, Seewann, Wolf, & Hacioglu, ). On account of EU legislation, in turn, EU citizens enjoy better access to the Austrian labour market and generate higher average incomes than other migrants (Statistics Austria, ).Human capital, as acquired by education and training , is paramount.…”
Section: Changing Social Stratification In Vienna: Potential Causes Omentioning
confidence: 99%
“…100 Turks have also become the main target of antiimmigrant political movements in Austria since the 1990s. 101 A survey conducted by the European Network Against Racism has found that in Austria 'people with a migrant background, even third-generation migrants, specifically of Turkish descent, are perceived as "foreigners" and face barriers in education . .…”
Section: Explaining Variation In Euro-turks' Voting Behaviourmentioning
confidence: 99%
“…Until the breakdown of the Eastern bloc in 1989, Austria mostly attracted migrants from Yugoslavia and Turkey. 4 Various studies show that those migrant groups have been targeted by discrimination and stigmatisation in both countries (Juhasz and Mey 2003;Fibbi et al 2006;Sievers et al 2014).…”
Section: Datamentioning
confidence: 99%